International Lifestyle Migration and Social marginalization on the Tourism Village - M Kolopaking, Lala (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTBy conducting qualitative research that supported with quantitative data analysis, it has founded that international lifestyle migration which committed by Middle East citizens (Saudi Arabian and Qatar) at South Tugu Village, Cisarua in East Java Indonesia as the destination for village tourism - have been raising social unequality. International lifestyle migration process on this village had occured along with international refugee resettlement from Asian country (Pakistan, Afganistan, Morocco,Myanmar ) which is inevitable became as a source of social change. It was begin by the growth of livelihood and economic behavior of local community itself that keenly more dependent on the tourism enterprises. The change of house building and settlement patterns were also followed by the transformation of land occupation and ownership. Moreover, it is identified by manner of speech, eating habits and also public order and security. However, apparently those changes are not enganging with the presence of social welfare equality. On the contrary, such development has been precisely marginalizing the poor community on the village.Keywords: international lifestyle migration, social change, inequality and social marginalization.ABSTRAKDengan melakukan penelitian kualitatif yang didukung dengan analisis data kuantitatif, diketahui bahwa migrasi gaya hidup internasional yang dilakukan oleh warga Timur Tengah (Arab Saudi dan Qatar) di bagian selatan Desa Tugu, Cisarua di Jawa Timur Indonesia sebagai salah satu tujuan untuk pariwisata - telah membesarkan sosial unequality. Proses migrasi gaya hidup internasional di desa ini telah terjadi seiring dengan datangnya turis internasional dari negara Asia (Pakistan, Afganistan, Maroko, Myanmar) yang tidak bisa dihindari menjadi sumber dari perubahan sosial. Itu dimulai dengan pertumbuhan mata pencaharian dan perilaku ekonomi masyarakat setempat itu sendiri yang menjadi lebih tergantung pada perusahaan pariwisata. Perubahan bangunan rumah dan pola pemukiman juga diikuti oleh transformasi pendudukan lahan dan kepemilikan. Selain itu, dapat diidentifikasi dari cara bicara, kebiasaan makan dan ketertiban umum serta keamanan. Namun, rupanya perubahan tersebut tidak mengikutsertakan dengan kehadiran kesetaraan kesejahteraan sosial. Sebaliknya, pembangunan tersebut telah meminggirkan masyarakat miskin di desa.Kata kunci: migrasi internasional gaya hidup, perubahan sosial, ketimpangan dan marginalisasi sosial.